Houses built on sand Sovereignty, violence and revolution in the Middle East - Mabon, Simon (Manchester University Press, 2020)
The events of the Arab Uprisings posed an existential challenge to sovereign power across the Middle East. Whilst popular movements resulted in the toppling of authoritarian rule in Tunisia, Egypt and Yemen, other regimes were able to withstand these pressures. This book questions why some regimes fell whilst others were able to survive.Drawing on the work of political theorists such as Agamben and Arendt, Mabon explores the ways in which sovereign power is contested, resulting in the fragmentation of political projects across the region. Combining an innovative theoretical approach with interviews with people across the region and beyond, Mabon paints a picture of Middle Eastern politics dominated by elites seeking to maintain power and wealth, seemingly at whatever cost. This, for Mabon, is a consequence of the emergence and development of particular visions of political projects that harness or marginalise identities, communities, ideologies and faiths as mechanisms designed to ensure their survival.This book is essential reading for those interested in understanding why the uprisings took place, their geopolitical consequences, and why they are likely to happen again.